Is laccase from medicinal mushroom Cerrena unicolor cytotoxic to colon cancer cell line CT-26? - Daria Sondej; Dominika Pigoń-Zając; Magdalena Jaszek; Dawid Stefaniuk; Anna Matuszewska; Kamil Bielak; Grzegorz Opielak; Teresa Małecka-Massalska; Mansur Rahnama-Hezavah; Monika Prendecka-Wróbel (PLoS ONE, 2025)
Introduction and objective Colorectal cancer takes an increasing toll every year. Despite the dynamic development of pharmacology, there is still no drug that would be strong enough to cause apoptosis of cancer cells, but at the same time would be free from numerous side effects. Taking traditional Eastern medicine into account, studies were carried out using an extract - laccase (LAC) from a medical mushroom called Cerrena unicolor- on CT-26 colon cancer cells. Preliminary cytotoxicity tests have already confirmed that the examined extract affects cancer cells and at the same time has no significant effect on L929 cells. The Electric Cell-substrate Impedance Sensing system (ECIS) and standard methods were used in this work. ECIS used in this study is an advanced in vitro impedance measuring system. Materials and methods The CT-26 and L929 cells were treated by five different concentrations of the LAC preparation ranging from 0.025 to 250 μg/mL. Concentrations selected for the ECIS system assay were: 0.25;2.5 and 250 μg/mL. The default optimal frequencies in the ECIS system for Resistance (R) 4000Hz, Impedance (Z) 16000Hz, Capacitance (C) 64000Hz were used. Resluts ECIS results demonstrate the potential anti-cancer activity of the laccase preparation against CT-26 cancer cells, and affect theL929 cells in to a lesser extent. Thanks to the use of the ECIS research technique, it was possible to monitor live changes in cell morphology and physiology, which translates into accurate conclusions about the action of the tested preparation.